PEMAHAMAN DASAR ANALISIS MODEL COMPUTABLE GENERAL EQUILIBRIUM (CGE) - Hayati, Mardiyah (Program Studi Agribisnis Fakultas Pertanian Universitas Trunojoyo Madura., 2013)
Simple paper about basic understanding of computable general equilibrium aimed to give basic understanding about CGE. It consist of history of CGE, assumption of CGE model, excess and lack of CGE model, and creation of simple CGE model for closed economy. CGE model is suitable to be used for seeing impact of new policy implementation. It is because CGE model use general equilibrium in which this theory of general equilibrium explaining about inter-relation among markets in the economy system. CGE model was introduced in 1960s known as Johansen model. Next, it is expanded into various models such as: ORANI Model, General Trade Analysis Project (GTAP) Model, and Applied General Equilibrium (AGE) Model. In Indonesia, there are CGE ORANI Model, Wayang, Indonesia-E3 and IRCGE. CGE Model is created by assumption of perfect competition. Consumer maximizes utility, producer maximizes profit, and company maximizes zero profit condition.